An estimate of the global budget and distribution of ethanol using a global 3-D atmospheric chemistry transport model STOCHEM-CRI. Issue 2 (4th May 2017) - Khan, M.A.H.; Glaubes, H.; Kent, A.; Harrison, T.G.; Foulds, A.; Percival, C.J.; Shallcross, D.E.
Abstract : The atmospheric global budget and distribution of ethanol have been investigated using a global 3-dimensional chemistry transport model, STOCHEM-CRI. Ethanol, a precursor to acetaldehyde and peroxyacetyl nitrate (PAN), is found throughout the troposphere with a global burden of 0.024–0.25 Tg. The atmospheric lifetime of ethanol is found to be 1.1–2.8 days, which is in excellent agreement with estimates established by previous studies. The main global source of ethanol is from direct emission (99%) and the remainder (1%) being produced via peroxy radical reactions. In terms of removal rates of ethanol in the atmosphere, oxidation by hydroxyl radicals (OH) accounted for 51%, dry deposition 8% and wet deposition accounted for 41%. Globally there are significant concentrations of ethanol over equatorial Africa, North America and parts of Asia with considerably higher concentrations modelled over Saudi Arabia and Eastern Canada. Through comparison of measured and modelled ethanol data, it is apparent that the underestimation of the source strength of ethanol and the coarse resolution of the STOCHEM-CRI model produce the discrepancies between the model and the measured data mostly in urban areas. The increased vegetation and anthropogenic emissions of ethanol lead to an increase in the production of acetaldehyde (by up to 90%) and peroxyacetyl nitrate (by up to 10%) which disrupts the NOx -ozone balance, promoting ozone production (by up to 1.4%) in the equatorial regions.